The effectiveness of using Kahoot media on the geography learning outcomes of eleventh-grade students at SMA Negeri 4 Sidenreng Rappang - Nurul Mughny HR; Madaling Madaling; Muhammad Takdir (Universitas Muhammadiyah Enrekang, 2025)
This study aims to determine the effectiveness of using Kahoot media on the geography learning outcomes of eleventh-grade students at SMA Negeri 4 Sidenreng Rappang. Kahoot is a technology-based learning platform that can enhance student engagement and motivation through interactive quizzes. The method used in this research is a quasi-experimental design with a pretest-posttest control group design. The research sample consisted of two classes: the experimental class, which used Kahoot media, and the control class, which used conventional learning methods. The instrument used was a multiple-choice learning outcome test administered before and after the treatment. The data analysis results showed a significant difference between the learning outcomes of students in the experimental class and those in the control class. The average post-test scores of students in the experimental class were higher than those in the control class. This indicates that the use of Kahoot media is effective in improving students' geography learning outcomes. Therefore, Kahoot can be used as an engaging and interactive alternative learning media to support the teaching and learning process in schools.